PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KEDISIPLINAN SISWA - Astutining Dyah Wulandari; Sri haryanto; Muhammad saefullah (JOURNAL SAINS STUDENT RESEARCH, 2025)
This Journal aims to: 1) To find out the role of Islamic Religious Education Teachers in forming Discipline in students at SD Negeri 02 Penanggungan Banjarnegara; 2) To find out the factors that support and hinder Islamic Religious Education Teachers in forming Discipline in students at SD Negeri 02 Penanggungan Banjarnegara.In writing this Journal, the author uses a descriptive research type with a qualitative approach, where this research is field-based. Data collection techniques used in this study use observation, interview, and documentation methods. Meanwhile, in the data analysis technique carried out with the aim of making it easier to understand the phenomena of problems that occur and in providing solutions to existing problems, the author uses the method of data reduction, data presentation, and drawing conclusions.It can be seen from the results of this study that: 1) Islamic Religious Education teachers play a very important role in forming student discipline with designed programs such as reciting Asmaul Husna which is carried out at 06:45-07.00 before learning takes place, after which it is continued with the habit of praying dhuha together before entering the classroom. 2) In addition to these programs, Islamic Religious Education teachers also apply discipline about wearing neat, clean uniforms and following learning according to the rules. This is evident from the quality of students who have been able to apply discipline at school. 3) Obstacles in implementing discipline include supporting and inhibiting factors. Supporting factors, the involvement of Islamic Religious Education teachers, other teachers, and parents in forming discipline both at home and at school by supervising student character. While the inhibiting factors are the lack of awareness of discipline and students often underestimate all the rules that have been applied at school, including parental supervision who does not care about children's discipline at home.